The influence of leadership style and work discipline on the performance of teachers on elementary schools - Juni Parantiku; Bukman Lian; Alhadi Yan Putra (Journal of Educational and Learning Studies, 2021)
The purposes of this study are to 1) find out and describe whether there is an influence of leadership style on teacher performance, 2) to find out and describe whether there is an influence of work discipline on teacher performance, and 3) to find out and describe whether there was an influence of leadership style and work discipline together on Performance of State Elementary School Teachers in Semendawai barat District. This study uses quantitative method. The researcher collects the data by using observation, interviews and questionnaires. The analysis that researcher do is the correlation analysis of the t test and the F test. The results of the data analysis from the questionnaire showed that there was an influence of leadership style on the performance of elementary school teachers in Semendawai barat subdistrict. Then, there is an influence of work discipline on the performance of State Elementary School Teachers in Semendawai barat District. And there is an influence of Leadership Style and Work Discipline together on the Performance of Elementary School Teachers in West Semendawai District. (significant level 5%).